Nanomaterials Trigger Functional Anti‐Tumoral Responses in Primary Human Immune Cells - Mittelheisser, Vincent; Lefebvre, Olivier; Banerjee, Mainak; Ghosh, Shayamita; Dupas, Amandine; Diringer, Marie‐Charlotte; Blumberger, Juliette; Bochler, Louis; Harlepp, Sébastien; Larnicol, Annabel; Pichot, Angélique; Stemmelen, Tristan; et al. (Advanced science, 2025)
Targeting the immune system with nanoparticles (NPs) to deliver immunomodulatory molecules emerged as a solution to address intra‐tumoral immunosuppression and enhance therapeutic response. While the potential of nanoimmunotherapies in reactivating immune cells has been evaluated in several preclinical studies, the impact of drug‐free nanomaterials on the immune system remains unknown. Here, the molecular and functional response of human NK cells and pan T cells to a selection of five NPs that are commonly used in biomedical applications are characterized. After a pre‐screen to evaluate the toxicity of these nanomaterials on immune cells, ultrasmall silica‐based gadolinium (Si‐Gd) NPs and poly(lactic‐ co ‐glycolic acid) (PLGA) NPs are selected for further investigation. Bulk RNA‐sequencing and flow cytometry analysis showcase that PLGA NPs trigger a transcriptional priming toward activation in NK and pan T cells. While PLGA NPs improved NK cells anti‐tumoral functions in a cytokines‐deprived environment, Si‐Gd NPs significantly impaired T cells activation as well as functional responses to a polyclonal antigenic stimulation. Altogether, PLGA NPs are identified as an attractive strategy for reactivating the immune system of cancer patients.